Extrastriate connectivity of the mouse dorsal lateral geniculate thalamic nucleus. Issue 9 (4th February 2019) - Bienkowski, Michael S.; Benavidez, Nora L.; Wu, Kevin; Gou, Lin; Becerra, Marlene; Dong, Hong‐Wei
Abstract: The mammalian visual system is one of the most well‐studied brain systems. Visual information from the retina is relayed to the dorsal lateral geniculate nucleus of the thalamus (LGd). The LGd then projects topographically to primary visual cortex (VISp) to mediate visual perception. In this view, the VISp is a critical network hub where visual information must traverse LGd–VISp circuits to reach higher order "extrastriate" visual cortices, which surround the VISp on its medial and lateral borders. However, decades of conflicting reports in a variety of mammals support or refute the existence of extrastriate LGd connections that can bypass the VISp. Here, we provide evidence of bidirectional extrastriate connectivity with the mouse LGd. Using small, discrete coinjections of anterograde and retrograde tracers within the thalamus and cortex, our cross‐validated approach identified bidirectional connectivity between LGd and extrastriate visual cortices. We find robust reciprocal connectivity of the medial extrastriate regions with LGd neurons distributed along the "ventral strip" border with the intergeniculate leaflet. In contrast, LGd input to lateral extrastriate regions is sparse, but lateral extrastriate regions return stronger descending projections to localized LGd areas. We show further evidence that axons from lateral extrastriate regions can overlap onto medial extrastriate‐projecting LGd neurons in the ventral strip, providing a putative subcortical LGd pathway for communication between medial and lateral extrastriate regions. Overall, our findings support the existence of extrastriate LGd circuits and provide novel understanding of LGd organization in rodent visual system. Abstract : Corticothalamic projecting neurons in the mouse dorsolateral geniculate thalamus. Novel extrastriate projections to VISam and VISpm were found localized to a ventral strip region adjacent to the border with the intergeniculate leaflet (IGL). Results are cross‐validated by systematic bidirectional tract tracing with anterograde/retrograde coinjections.